How COVID-19 Continues to Affect Lives of Refugees in Kenya : Rapid Response Phone Survey Rounds 1 to 5 - Pape, Utz; Delius, Antonia (World Bank, Washington, DC, 2021)
Understanding the socioeconomic impact of the COVID-19 pandemic on refugees is important to inform targeted policy responses. The arrival of COVID-19 disrupted lives across all countries and communities, creating unprecedented challenges for the world. As of August 2021, there have been more than 200,000 cases in Kenya, with more than 4,000 deaths. In response, the Government of Kenya (GoK) has imposed a range of restrictions to curb the spread of the pandemic. However, this has inadvertently resulted in socioeconomic effects on the population in Kenya, including those in refugee settlements. Data from the Rapid Response Phone Surveys (RRPS) will be essential in providing information to monitor and mitigate the impact of the pandemic. For refugee and surrounding host communities, which span the humanitarian development nexus, this type of data is particularly important as comparatively there is the least data globally for these populations have. The Kenya COVID-19 RRPS aims to fill socioeconomic data gaps by providing evidence to inform targeted policy and programmatic response. With face-to-face data collection no longer a feasible option due to high infection rates and government restrictions, phone surveys emerged as an alternative for rapid and frequent data collection. The World Bank in collaboration with the Kenya National Bureau of Statistics (KNBS), the United Nations High Commissioner for Refugees (UNHCR) and researchers from the University of California, Berkeley, are implementing Rapid Response Phone Surveys for (i) Kenyan and refugee households, (ii) micro-enterprises run by young entrepreneurs, and (iii) formal enterprises. This note provides findings and makes policy recommendations based on five waves of data collection for Kenyan and refugee households. The RRPS data is unique as it allows to draw a picture of the socioeconomic situation of all major refugee groups in Kenya during the COVID-19 pandemic, covering camp and urban refugees as well as stateless persons in the same as Kenyan nationals. Kenyan nationals residing in urban areas were selected as the comparison group throughout this report, as densely populated areas, such as Kenya’s urban areas and refugee camps, were differently affected by the pandemic and thus this comparison is relatively easily made.